RELATIONSHIP BETWEEN PEER ATTACHMENT WITH KOREAN WAVE CULTURAL CONFORMITY IN EARLY YOUTH - Garnika, Dikdik (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2019)
The Korean wave cultural conformity that occurred in early adolescents was triggered because of a close relationship in friendship which made him adjust his behaviour with his peer group. This study aims to describe empirically the relationship of peer attachment with Korean wave culture conformity of students. The research uses a quantitative approach with correlational methods. The samples used were saturation samples, namely all students of class 7th grade SMP Negeri 44 Bandung Academic Year 2018/2019 who enjoyed Korean wave culture in the form of Korean pop and Korean drama totalling 88 people. Data collection techniques using peer attachment instruments adapted from the inventory of parents and peer attachment-revised and the Korean wave cultural conformity instruments developed by researchers. The results showed that in general, the peer attachment of students was in the category of secure attachment and Korean wave cultural conformity of students was in the category of obedience. This study recommends basic group guidance services that can improve the achievement of peer attachments and can reduce the Korean wave cultural conformity of students.